Modelling the volatility of crude oil returns : Jumps and volatility forecasts - Dutta, Anupam; Bouri, Elie; Roubaud, David (John Wiley and Sons, 2020)
We contribute to the scarce literature on the oil market volatility index (OVX) by examining the presence of time‐varying jumps in OVX and by assessing the ability of OVX to predict the conditional variance of crude oil returns. Using a GARCH‐jump model, we find evidence that OVX is characterized by jump behaviour that tends to vary over time. Further analysis indicates that accounting for the jump behaviour of OVX helps improve the conditional variance forecasts of crude oil returns. Since the studied features of OVX play a crucial role in asset pricing and risk analyses, our findings have policy implications related to refining volatility prediction models and risk measures.
Keywords: conditional variance; GARCH‐jump; OVX; time‐varying jumps; volatility forecasts; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|